Excessive Blood Pressure Rise and Cardiovascular Remodeling in Marathon Runners - Gwag, Hye Bin; Kim, Young-Joo; Park, Kyoung-Min (International Journal of Sports Medicine, 2024)
Exercise-induced hypertension (EIH) is thought to be associated with increased cardiovascular (CV) risks. However, no previous studies have investigated the effects of EIH on CV systems in marathon runners without CV risk factors using both 24-hr ambulatory blood pressure (BP) monitoring and exercise stress echocardiography (ESE). This study firstly described differences in CV adaptations according to EIH assessed by both exams. Marathon runners between 35 and 64 years of age without CV risk factors were eligible. All the participants underwent both 24-hr ambulatory BP monitoring and ESE. EIH was defined as a maximal exercise systolic BP≥210 mmHg. The EIH group (n=19) had shorter training history and higher exercise intensity compared to the non-EIH group (n=23). The average systolic BP was higher in the EIH group than in the non-EIH group. Left cardiac chamber size and left ventricular mass (LVM) were also higher in the EIH group compared to the non-EIH group. Maximal BP during ESE was positively correlated with both parameters. Exaggerated BP response during exercise needs to be monitored for pre-emptive measurements before it results in progressive cardiovascular maladaptation.
Keywords: marathon; exercise-induced hypertension; cardiac remodeling; 24-hour ambulatory blood pressure; exercise stress echocardiography